CP-ABE with Hidden Policy from Waters Efficient Construction. (28th January 2016) - Wang, Zhiwei; He, Mingjun
Abstract : ABE provides a good way for access controlling in cloud computing. However, in many application scenarios, access policies for encryption also should be protected since they may directly contain sensitive information. For example, in smart grid, the access policies may contain the private information about underlying data, data owner or the data recipients, and disclosing some sensitive access policies could result in negative publicity, or loss of market revenue. In this paper, we present a CP-ABE scheme with hidden policy from Waters efficient construction. In our scheme, the access policy is hidden by using the composite order bilinear groups and can be expressed with LSSS. Our scheme is proved CPA secure under four statics assumptions.